SAFETY, IDENTITY AND CONSENT: A LIMITED DEFENSE OF REPRODUCTIVE HUMAN CLONING - Lane, Robert (Bioethics, 2006)
Some opponents of reproductive human cloning have argued that, because of its experimental nature, any attempt to create a child by way of cloning would risk serious birth defects or genetic abnormalities and would therefore be immoral. Some versions of this argument appeal to the consent of the person to be conceived in this way. In particular, they assume that if an experimental reproductive technology has not yet been shown to be safe, then, before we use it, we are morally obligated to get either the actual consent or the presumed consent of the person to be conceived. In this article, I attempt to explain the appeal of such consent-based arguments as deriving from a mistaken view of personal identity. I then argue that since this view is false, such arguments are unsound. Finally, I argue that even if reproductive cloning is unsafe, it may still be morally permissible in some circumstances.